Short Communication: Bird correlations with waste in Muara Gembong, West Java, Indonesia - Selsa Artika Ayujawi; Nurul Laksmi Winarni; Dimas Haryo Pradana (Society for Indonesian Biodiversity, 2021)
Abstract. Ayujawi SA, Winarni NL, Pradana DH. 2021. Short Communication: Bird correlations with waste in Muara Gembong, West Java, Indonesia. Biodiversitas 22: 3872-3879. The existence of waste in Muara Gembong can potentially affect bird abundance because organic waste can be a source of bird food, while inorganic waste can cause changes in habitat structure. This study aimed to (i) determine bird species that have a high abundance near the trash, and (ii) determine the correlation between waste concentration and the relative abundance of birds. The study was conducted in June 2020 in Pantai Mekar and Muara Blacan areas, Muara Gembong, West Java. Bird observation was carried out using exploration method and the relative abundance of the bird was determined based on encounter rates. The data collection and calculation of waste concentration were carried out following the NOAA protocol. The Spearman correlation test was carried out between the abundance of each bird species and the concentration of waste. Our results suggested that 26 species of birds in Muara Gembong were found near trash and 24 species have negative correlations to inorganic waste. The Javan munia (Lonchura leucogastroides) and Great egret (Egretta alba) were the most abundant species living near the trash with encounter rates of 39.13 and 38.89, respectively. Moreover, the concentration of inorganic waste has a significant negative correlation to the relative abundance of Cerulean kingfisher (Alcedo coerulescens), Spotted dove (Streptopelia chinensis), and Sunda collared dove (Streptopelia bitorquata). Based on these findings, inorganic waste in Muara Gembong can significantly reduce the abundance of birds in the long term because the pile of inorganic waste may cause damage to the mangrove forest, which is a bird habitat.